2020
DOI: 10.7554/elife.61820
|View full text |Cite
|
Sign up to set email alerts
|

Reading the epigenetic code for exchanging DNA

Abstract: Three independent studies show that a protein called ZCWPW1 is able to recognize the histone modifications that initiate the recombination of genetic information during meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…39,40 ZCWPW1, a reader of histone (H3) modifications, is required to initiate the recombination of genetic information during meiosis. 41 In addition, transcriptomic variations observed in the present study also suggest that the HH diet affects the post-transcriptional regulation of oocyte gene expression, as several differentially expressed genes have been implicated in ribosomal processing like RARS, 42 RIOK1 43 and MRPL55. 44,45 Thus, maternal HH diet altered oocyte transcripts content of genes involved in meiosis and translational control, suggesting difficulties to achieve meiosis and to support the embryo development.…”
Section: Discussionsupporting
confidence: 53%
“…39,40 ZCWPW1, a reader of histone (H3) modifications, is required to initiate the recombination of genetic information during meiosis. 41 In addition, transcriptomic variations observed in the present study also suggest that the HH diet affects the post-transcriptional regulation of oocyte gene expression, as several differentially expressed genes have been implicated in ribosomal processing like RARS, 42 RIOK1 43 and MRPL55. 44,45 Thus, maternal HH diet altered oocyte transcripts content of genes involved in meiosis and translational control, suggesting difficulties to achieve meiosis and to support the embryo development.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, three independent groups found that the histone methylation reader ZCWPW1 could specifically recognize dual histone methylation marks (H3K4me3 and H3K36me3) deposited by PRDM9 at recombination hotspots in mice [47][48][49][50]. Much less is known about how ZCWPW1 reads these epigenetic marks and thus participates in the meiotic recombination process to promote DSB repair [51].…”
mentioning
confidence: 99%